Effects of Dietary Bacillus and Non-starch Polysaccharase on the Intestinal Microbiota and the Associated Changes on the Growth Performance, Intestinal Morphology, and Serum Antioxidant Profiles in Ducks - Peng, Simin; Wang, Xin; Wang, Yuyu; Lv, Tuo; Zhao, Haohan; Wang, Yanzhou; Zhu, Siyuan; Qiu, Huajiao; Zeng, Jianguo; Dai, Qiuzhong; Lin, Qian (Frontiers in Microbiology, 2021)
Given the desirable results of using probiotics and enzyme preparations as feed supplements in poultry health, here, the effects of Bacillus and Non-starch Polysaccharase (NSPase) on the growth performance, serum antioxidant profiles, and gut microbial communities of early stage ducks is investigated. A total of 400 Zhijiang ducks (of similar body weight and 1 day age) was selected and randomly divided into four groups. The feeding period was 28 days. Each group contained 10 replicates of 10 birds. Control group (I) was fed with basal diet, while treatment groups II to IV were fed, respectively, with 150 mg/kg NSPases, 25 mg/kg Bacillus probiotics, and 150 mg/kg NSPases + 25 mg/kg Bacillus probiotics in their basal diet. The results demonstrated that dietary Bacillus (25 mg/kg) increased average final weight, average daily gain (ADG), and decreased the malonaldehyde (MDA) in birds (P < 0.05). Dietary Bacillus (25 mg/kg) and NSPases + Bacillus (150 mg/kg + 25 mg/kg) presented much higher glutathione (GSH) and activities of superoxide dismutase (SOD) in birds (P < 0.05). Additionally, as revealed by β-diversity indices and analysis of similarities, dietary NSPases + Bacillus could affect the ileum microbial abundances and diversities at the genera level (P < 0.05), but it had no effect on the caecal microbiota. Also, 16S rRNA sequencing revealed that dietary Bacillus and NSPases + Bacillus increased the populations of Ruminococcaceae genera in the cecum (P < 0.05), and S24-7_group and Lactobacillus genera in the ileum (P < 0.05). However, dietary NSPases and Bacillus alone and in combination could significantly decrease the content of Bacteroides in the ileum (P < 0.05). According to Spearman correlation analysis, 7 ilea bacterial microbiomes (S24-7 group, Lactobacillus, Subgroup 2, Subgroup 1, Kitasatospora, Candidatus Solibacter, and Akkermansia) were positively correlated with SOD (P < 0.05). In conclusion, Bacillus (25 mg/kg) and NSPases (150 mg/kg) included in the diet could efficiently enhance the growth performance by altered gut microbiota composition at the genera level and antioxidant indices of ducks.